Analysis of Customer Satisfaction with Currency Services in Using the Brilink Agent Website Using the Webqual 4.0 Method at Bank BRI Palembang Branch - Davesela, Meidick Dias; Sutabri, Tata (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The Brilink agent website has utilized the website in public services. During publication, there are still problems in terms of usability quality such as features on the menu bar not functioning properly, from the quality of information, it was found that there was an error display on each information about Brink customers in the city of Palembang and from the quality of service interactions there was no error notification when entering data on email. In this study, the quality of the brilink palembang agent website can measured using Webqual 4.0 method with multiple linear regression analysis. The result of this study is that this website has satisfied customers in KUR Services based on the accepted two hypotheses on the brilink Agent Website is a Website that can be accessed by all internet users or anyone with a Home link (bri.co.id) The purpose of measuring the quality of this Website is to find out how good or lack of Website services according to its users using the Webqual 4.0 method. Webqual 4.0 is a method used to measure the quality of a Website based on the end user. Webqual is compiled in research on 3 dimensions, namely Usabillity, Information and Service Interaction, this study aims to determine the quality of Website Home (bri.co.id) to determine the level of service satisfaction. This study uses respondents and statements with validity tests obtained R calculate > from r table and reliability tests obtained alpha values greater than R tables, then the precision R table is declared Valid.on the Likert test scale it is known that the dimensions or indicators of usabillity get the most level of Usabillity so that the Usabilllity dimension has a positive effect on user satisfaction.